Deep learning applications and intelligent decision making in engineering - Senthilnathan, Karthikrajan 1991-; Shanmugam, Balamurugan 1985-; Goyal, Dinesh 1976-; Annapoorani, Iyswarya 1976-; Samikannu, Ravi 1982- (A volume in the Advances in computational intelligence and robotics (ACIR) book series, 2021)
"This book explores the application of deep learning in building a smart world, ranging from smart cities, smart agriculture to smart homes" - Provided by publisher